Volume and temperature change behaviors of photothermal convertible hydrogels. (5th May 2017) - Nakamura, Shunsuke; Onimaru, Shohei; Oishi, Yushi; Narita, Takayuki
Abstract: Photoresponsive behaviors of thermosensitive hydrogels containing carbon black (CB) were investigated by comparing experimental and simulation results. Poly( N -isopropylacrylamide-acrylamide) (PNIPAm) and poly( N -n-propyl-acrylamide) (PNNPAm) gels were employed as the matrix of photoresponsive hydrogels exhibiting a lower critical solution temperature (LCST) behavior without hysteresis and with hysteresis, respectively; CB-PNIPAm and CB-PNNPAm were used as photoresponsive hydrogels. The size and surface temperature behaviors of the photoresponsive hydrogels were measured under laser irradiation. The surface temperatures of irradiated both gels increased rapidly after the irradiation to a peak and then decreased exponentially. The CB-PNIPAm gel shrank and its size synchronized with the surface temperature rise and reached a constant between the shrunken and swelling states. The CB-PNNPAm gel first shrank, then re-swelled after going through a minimum value. The main different behaviors of the two gels could be explained by the hysteresis effect based on numerical simulation results. The numerical simulation results also demonstrated that photosensitive gels with hysteresis can be self-oscillator driven by stationary light sources. Graphical abstract: Highlights: Photosensitive volume change behaviors are different between gels with and without hysteresis.. Light irradiation can be pinned the photosensitive gels in the unstable phase. Hysteresis allows ideal photosensitive gels to oscillate in volume and temperature under a stationary light beam.